Antimicrobial Activity of Ag:ZnO/Chitosan Composites - Mariana (BUȘILĂ) IBĂNESCU; Dana TUTUNARU; Viorica MUȘAT (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2014)
This paper deals with Ag, ZnO and Ag-doped ZnO nanoparticles embedded in chitosan (CS) matrix, prepared by hydrolysis of zinc acetate in isopropanol in the presence of lithium hydroxide (LiOH) in low temperature conditions. The nanoparticles embedded in the chitosan matrix were characterised by Xray diffraction (XRD) and scanning electron microscopy (SEM). The antimicrobial activity of Ag/CS, ZnO/CS and Ag:ZnO/CS composites with respect to simple CS polymer was investigated by using the paper disc method on Mueller-Hinton agar without blood against the Gram-negative bacteria, Escherichia coli (E. coli) and the Gram-positive bacteria, Staphylococcus aureus (S. Aureus) on Mueller-Hinton agar with blood. The nanocomposites materials showed good antimicrobial activity, that recommends them for applications in medical and food packaging fields.